Successful Public Policy in the Nordic Countries 2022
DOI: 10.1093/oso/9780192856296.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

‘Living Longer, Working Longer’

Abstract: With the Danish life expectancy indexing of pensionable ages as case, this chapter examines to what extent a policy that objectively can help avoid recurrent conflicts as well as large economic and social challenges, can be deemed a success, even though it fits poorly with the PPPE model, as it was adopted, tightened, and continued without involving major stakeholders, and is neither fair nor popular. After briefly introducing the demographic challenges to pensions and explaining the positive potential of link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In fact, the reform did not just seek to secure the sustainability of the pension system, but aimed more widely at tackling budget deficits in the decades where aging peaks. As such it became an integral part of long‐term public budget planning, which turned out to secure its survival through several changes of governments and occasional eruptions of conflicts over retirement policy (von Nordheim & Kvist, 2022b).…”
Section: Regulation Of Retirement Agesmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the reform did not just seek to secure the sustainability of the pension system, but aimed more widely at tackling budget deficits in the decades where aging peaks. As such it became an integral part of long‐term public budget planning, which turned out to secure its survival through several changes of governments and occasional eruptions of conflicts over retirement policy (von Nordheim & Kvist, 2022b).…”
Section: Regulation Of Retirement Agesmentioning
confidence: 99%
“…A broad international literature indicates that health and remaining working capacity tend to improve at a markedly slower rate than average life expectancy. Consequently, we have elsewhere argued that a life expectancy indexing of the pensionable age like the Danish will increase social inequality among older workers and pensioners since the ability to postpone retirement and work longer—as well as remaining life expectancy itself—are very unequally distributed among occupations and across individuals (von Nordheim & Kvist, 2022a, 2022b). Similarly, we have suggested that the economic benefits of raising the pensionable age will decrease as the age go up and that certain age thresholds may prove difficult to transcend for social as well as biological reasons.…”
Section: The Implicit Understanding Of Retirement In the Various Refo...mentioning
confidence: 99%
See 3 more Smart Citations